Experimental investigation on Geopolymer Fly Ash Building Brick by Atmospheric Curing - Muduli, S. D.; Nayak, B. D.; Mishra, B. K. (Recent Trends in Chemical and Material Sciences Vol. 2, 2021)
The goal of the current program is to develop geopolymer fly ash building bricks that cure in the atmosphere. Fly ash and an alkaline soda-based chemical activator solution are used to make geopolymer construction bricks in the presence of sodium silicate and water, with a different Na2O/(Al2O3+SiO2) ratio maintained. Under atmospheric curing, 230 mm x 110 mm x 75 mm fly ash building bricks are formed. After 25 days of atmospheric curing the results shows that the geopolymer fly ash building bricks attain a crushing strength of 10 to 12 Mpa.